The Issue of Family and Education in The Works of Eastern Scientists (Zien Journal of Social Sciences and Humanities, 2021)
Education, upbringing and morality were the main content of almost all the works created by our ancestors over the centuries. This article reveals to what extent the Eastern scholars paid attention to family and upbringing issues, their work in this area and the main issues in it. Also, through the images of national heroes Shirok, Tomaris, Alpomish, Jaloliddin Manguberdi, such qualities as devotion to his people, love for the Motherland, courage and devotion, friendship and devotion were described. Particular attention is paid to the views on education of many scientists, such as Imam Bukhari, Al-Hakim at-Termizi, Beruni, Ibn Sina, Farabi, Khorezmi, and Fergani.